Demandas de poder no conselho pedagógico - reflexões a partir de um estudo de caso num agrupamento de escolas - Daniela Vilaverde e Silva (Universidade do Minho, 2008)
This article focuses on a study that took place in the school year of 2002/2003. The study is about the different games of power and interests moved by the actors from one of the administrative structure of the public basic schools: the pedagogic board. The implementation of a legal system of administrating schools by the Decree Law nr 115-A/98 brought changes to the pedagogic board composition. Thus, the plurality of actors, due to both its legal composition and to the creation of the schools grouping, gave a more complexity to this board. From a case study in a schools grouping, we pretend, on one hand, to analyse different powers among the pedagogic board members. On the other hand, to reflect on how the teachers see the participation of the different actors of this board. The data obtained from the investigation shows the existence of different relationships of power among the members of this board. The decisions, the procedures and practises adopted by the grouping mirror, above all, a greater predominance of the teachers interests of the 2nd and 3rd cycles comparing with the kindergartens and teachers of the 1st cycle, developing, in this way, cycles interests which may fragile dynamics connoted with the democratic logics